Higher loop renormalization of a supersymmetric field theory - Bellon, Marc P. (2007)
Using Dyson-Schwinger equations within an approach developed by Broadhurst and Kreimer and the renormalization group, we show how high loop order of the renormalization group coefficients can be efficiently computed in a supersymmetric model.